Analisis Rasio Likuiditas, Solvabilitas, Aktivitas Dan Profitabilitas Dalam Menilai Kinerja Keuangan Perusahaan - Tarsija Tarsija; Pandaya Pandaya (STIE Muhammadiyah Jakarta, 2020)
This research is a case study with research objects namely PT. Indonesian Pilot Pen. The collection technique is done by documenting the financial statements covering the balance sheet, income statement and cost of goods sold. In measuring the company's financial performance, data analysis techniques namely financial ratio analysis include 1). Liquidity (Current Ratio, Quick Ratio, and Cash Ratio) 2). Solvency (Debt to Assets Ratio and Debt to Equity Ratio), (3). Activities (Fixed Assets Turnover, Inventory Turnover) and (4). Profitability (Gross Profit Margin, Net Profit Margin and Return on Equity) in 2012-2016 by comparing the ratio of industry standards.Based on the results of research and analysis shows that 1). Financial Performance of PT. Indonesian Pilot Pen during 2012-2016 in terms of liquidity shows that this result with each of the indicators in the category is quite good (liquid). 2). The results of the financial performance research show that each of these indicators is in a fairly good category (solvable. Furthermore, Financial Performance in terms of Activities in the Fixed Turnover and Inventory Turnover in 2012-2016 these results indicate fluctuations from year to year and are categorized as not good (inefficient). Financial Performance in terms of Profitability in Gross Profit Margin, Net Profit Margin and Return on Equity in 2012-2016 These results show fluctuations from year to year and are categorized as not good (inefficient).